2020
DOI: 10.1002/anie.202005181
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 3‐Fluorochromanes via Iodine(I)/Iodine(III) Catalysis

Abstract: The chromane nucleus is common to a plenum of bioactive small molecules where it is frequently oxidized at position 3. Motivated by the importance of this position in conferring efficacy, and the prominence of bioisosterism in drug discovery, an iodine(I)/iodine(III) catalysis strategy to access enantioenriched 3‐fluorochromanes is disclosed (up to 7:93 e.r.). In situ generation of ArIF2 enables the direct fluorocyclization of allyl phenyl ethers to generate novel scaffolds that manifest the stereoelectronic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 85 publications
1
41
0
Order By: Relevance
“…value (Scheme 15). [33] X-ray crystallographic analyses of representative products revealed that the conformations of 77 enabled stabilizing stereoelectronic interactions, which render these molecules potentially valuable as drug candidates. Mechanistic interrogation of the reaction using deuterated probes showed that the process is stereospecific and likely proceeds through a type II inv pathway (Scheme 15).…”
Section: Amino- Oxy-or Carbofluorination Of Alkenesmentioning
confidence: 99%
See 3 more Smart Citations
“…value (Scheme 15). [33] X-ray crystallographic analyses of representative products revealed that the conformations of 77 enabled stabilizing stereoelectronic interactions, which render these molecules potentially valuable as drug candidates. Mechanistic interrogation of the reaction using deuterated probes showed that the process is stereospecific and likely proceeds through a type II inv pathway (Scheme 15).…”
Section: Amino- Oxy-or Carbofluorination Of Alkenesmentioning
confidence: 99%
“…Initially, selectfluor-mediated oxidation of iodoresorcinol catalyst in the presence of amine • HF in situ generates the transient difluoroiodoarene (78-I). [33] Ligand exchange at the iodine center of 78-I with alkene (76 a) and concomitant cyclization of 78-II occur in an enantioselective way by stabilizing aromatic interactions. Nucleophilic displacement of 78-III by fluoride ion eventually provides the relative syn-configuration and stereospecificity that was determined by the detailed NMR analysis, accomplishing the catalytic cycle.…”
Section: Amino- Oxy-or Carbofluorination Of Alkenesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Gilmour and co-workers utilized another chiral aryliodine 5j instead of previous catalyst 8a to accomplish the enantioselective fluorocyclization of allyl phenyl ethers 54 (Scheme 21). 37 The terminal aliphatic alkenes 54 underwent direct cyclization in the presence of catalytic chiral aryliodine 5j and excess oxidant Selectfluor, which resulted in hypervalent ArIF 2 generation in situ, to afford 3-fluorochromanes 55 in good yields and enantioselectivities (up to 67% yield, 86% ee). In this catalytic strategy, under identical conditions subtle structural changes on the C=C bond affected the stereoselectivity in a striking manner, for example 4-bromophenyl methallyl ether gave the corresponding product in 51% yield and only 10% ee (see Scheme 21).…”
Section: Short Review Synthesismentioning
confidence: 99%